2018
DOI: 10.1177/2167479518808237
|View full text |Cite
|
Sign up to set email alerts
|

Framing the Paralympic Games: A Mixed-Methods Analysis of Spanish Media Coverage of the Beijing 2008 and London 2012 Paralympic Games

Abstract: In recent years, there has been an increased emergence of studies focusing on the media coverage of the Paralympic Games. Until recently, studies have predominately used quantitative content analyses that, although providing useful interrogation of observational patterns, limit the understanding of and appreciation for the contexts that may have shaped the production of information. By focusing exclusively on the “what” and on the “how much,” it is difficult to reveal the “why” and to identify the underlying m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 64 publications
0
29
0
3
Order By: Relevance
“…Research also has used the media frames approach to examine how adaptive sports are covered in the media (Maika & Danylchuk, 2016; Misener, 2013; Solves et al, 2018). Some media frames research emphasizes the societal ideologies, power of news organizations, and journalists’ professional values, attitudes, and individual characteristics, as part of a hierarchical model of influences on news framing (Shoemaker & Reese, 1996).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Research also has used the media frames approach to examine how adaptive sports are covered in the media (Maika & Danylchuk, 2016; Misener, 2013; Solves et al, 2018). Some media frames research emphasizes the societal ideologies, power of news organizations, and journalists’ professional values, attitudes, and individual characteristics, as part of a hierarchical model of influences on news framing (Shoemaker & Reese, 1996).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some media frames research emphasizes the societal ideologies, power of news organizations, and journalists’ professional values, attitudes, and individual characteristics, as part of a hierarchical model of influences on news framing (Shoemaker & Reese, 1996). For example, a recent study concluded that the coverage of the Beijing and London Paralympics was obstructed by organizational and structural controls, editorial attitudes of the Paralympics being less important than the Olympics, production issues (i.e., time differences, available editorial space), and economic limitations (Solves et al, 2018). These financial, personal, and editorial influences compound an ideological pattern in society that stigmatizes people with disabilities.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Para alguns jornalistas, o esporte paraolímpico e os atletas paraolímpicos são uma espécie de "sub-representação esportiva", pois possuem baixa popularidade e supostamente têm pouco teor competitivo e atlético (GOLDEN, 2003;SOLVES et al, 2018). Para atletas paraolímpicos, por sua vez, existe um despreparo de parte dos jornalistas esportivos que cobrem o esporte para pessoas com deficiência.…”
unclassified